It's All Squares 2

Geometry Level 4

Let n n be a positive integer.

Equilateral A B C \triangle{ABC} has a side length of 1 1 and the n n inscribed squares have side lengths a , 2 a , . . . n a a, 2a, ... na as shown above.

Let A T A_{T} be the total area of the n n squares.

Find the value of n n for which A T a = 18 ( 2 3 1 ) 11 3 \dfrac{A_{T}}{a} = \dfrac{18(2\sqrt{3} - 1)}{11\sqrt{3}} .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rocco Dalto
Sep 28, 2020

tan ( 6 0 ) = 3 = a x x = a 3 \tan(60^{\circ}) = \sqrt{3} = \dfrac{a}{x} \implies x = \dfrac{a}{\sqrt{3}}

and

tan ( 6 0 ) = 3 = n a y y = n 3 a \tan(60^{\circ}) = \sqrt{3} = \dfrac{na}{y} \implies y = \dfrac{n}{\sqrt{3}}a

a ( n + 1 3 + n ( n + 1 ) 2 ) = 1 \implies a(\dfrac{n + 1}{\sqrt{3}} + \dfrac{n(n + 1)}{2}) = 1 \implies a ( n + 1 ) ( 2 + 3 n ) = 2 3 a(n + 1)(2 + \sqrt{3}n) = 2\sqrt{3}

a = 2 3 ( n + 1 ) ( 2 + 3 n ) \implies a = \dfrac{2\sqrt{3}}{(n + 1)(2 + \sqrt{3}n)}

\implies

A T = a 2 j = 1 n j 2 = a 2 n ( n + 1 ) ( 2 n + 1 ) 6 A_{T} = a^2\sum_{j = 1}^{n} j^2 =a^2\dfrac{n(n + 1)(2n + 1)}{6} \implies

A T a = a n ( n + 1 ) ( 2 n + 1 ) 6 = n ( 2 n + 1 ) 3 ( 2 + 3 n ) = 18 ( 2 3 1 ) 11 3 \dfrac{A_{T}}{a} = a\dfrac{n(n + 1)(2n + 1)}{6} = \dfrac{n(2n + 1)}{\sqrt{3}(2 + \sqrt{3}n)} = \dfrac{18(2\sqrt{3} - 1)}{11\sqrt{3}}

11 n ( 2 n + 1 ) = 18 ( 2 3 1 ) ( 2 + 3 n ) \implies 11n(2n + 1) = 18(2\sqrt{3} - 1)(2 + \sqrt{3}n)

22 n 2 + 11 n = 18 ( 4 3 2 ) + 18 ( 6 3 ) n \implies 22n^2 + 11n = 18(4\sqrt{3} - 2) + 18(6 - \sqrt{3})n \implies

22 n 2 ( 97 18 3 ) n ( 72 3 36 ) = 0 n = 4 , n = 9 ( 2 3 1 ) 22 22n^2 - (97 - 18\sqrt{3})n - (72\sqrt{3} - 36) = 0 \implies n = 4, n = -\dfrac{9(2\sqrt{3} - 1)}{22}

Since n n is a positive integer we choose n = 4 \boxed{n = 4}

Interesting - the ratio n A T a 2 \frac{nA_T}{a^2} tends to a nice limit as n n \to \infty .

Chris Lewis - 8 months, 2 weeks ago
Chew-Seong Cheong
Sep 29, 2020

Let the two ends of line A C AC not covered by the bases of squares be x \red x and y \red y as shown in the figure. Then x = a cot 6 0 = a 3 x = a \cot 60^\circ = \dfrac a{\sqrt 3} and y = n a cot 6 0 = n a 3 y = na \cot 60^\circ = \dfrac {na}{\sqrt 3} . From A C = 1 AC=1 , we have:

a 3 + a + 2 a + 3 a + + n a + n a 3 = 1 a 3 + n ( n + 1 ) a 2 + n a 3 = 1 ( n + 1 ) ( n 2 + 1 3 ) a = 1 ( n + 1 ) ( 3 n + 2 ) a 2 3 = 1 a = 2 3 ( n + 1 ) ( 3 n + 2 ) \begin{aligned} \frac a{\sqrt 3} + a + 2a + 3a + \cdots + na + \frac {na}{\sqrt 3} & = 1 \\ \frac a{\sqrt 3} + \frac {n(n+1)a}2 + \frac {na}{\sqrt 3} & = 1 \\ (n+1)\left(\frac n2 + \frac 1{\sqrt 3}\right)a & = 1 \\ \frac {(n+1)(\sqrt 3n+2)a}{2\sqrt 3} & = 1 \\ \implies a & = \frac {2\sqrt 3}{(n+1)(\sqrt 3n+2)} \end{aligned}

Now we have A T = a 2 + ( 2 a ) 2 + ( 3 a ) 2 + + ( n a ) 2 = n ( n + 1 ) ( 2 n + 1 ) 6 a 2 A_T = a^2 + (2a)^2 + (3a)^2 + \cdots + (na)^2 = \dfrac {n(n+1)(2n+1)}6a^2 . And

A T a = 18 ( 2 3 1 ) 11 3 n ( n + 1 ) ( 2 n + 1 ) 6 a = 18 ( 2 3 1 ) ( 2 3 + 1 ) 11 3 ( 2 3 + 1 ) n ( n + 1 ) ( 2 n + 1 ) 6 2 3 ( n + 1 ) ( 3 n + 2 ) = 18 11 11 ( 6 + 3 ) n ( 2 n + 1 ) 3 ( 3 n + 2 ) = 18 6 + 3 n ( 2 n + 1 ) 3 n + 2 3 = 36 12 + 2 3 n = 4 \begin{aligned} \frac {A_T}a & = \frac {18(2\sqrt 3-1)}{11\sqrt 3} \\ \frac {n(n+1)(2n+1)}6a & = \frac {18(2\sqrt 3-1)(2\sqrt 3+1)}{11\sqrt 3(2\sqrt 3+1)} \\ \frac {n(n+1)(2n+1)}6 \cdot \frac {2\sqrt 3}{(n+1)(\sqrt 3n+2)} & = \frac {18 \cdot 11}{11(6+\sqrt 3)} \\ \frac {n(2n+1)}{\sqrt 3(\sqrt 3n+2)} & = \frac {18}{6+\sqrt 3} \\ \frac {n(2n+1)}{3n+2\sqrt 3} & = \frac {36}{12+2\sqrt 3} \\ \implies n & = \boxed 4 \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...